Study of techniques of class schedule/timetable retrieval via SMS for students convenience - Yahya, Yazriwati; Nik Mahamood, Nik Maria (Universiti Teknologi Malaysia, 2006)
Short Messaging Services (SMS) is a service for transmitting text messages between mobile phones and also external systems such as electronic mail, paging and voice mail systems. In today's digital age, this service has becomes a valuable and effective tool for the students and lecturers in education environment. Some universities have used the SMS technology to improve the effectiveness of their services such as exam result notification, class cancellation, class changes, appointment reminders, class schedules and so forth. With SMS, students and lecturers can be reached in anywhere and anytime with ensuring that message is delivered. The SMS class schedule is a way to provide a service for students to retrieve their class schedule or timetable faster and cost effective. This service also can increase convenience for the students because the information comes to them immediately and effectively rather than having to seek them on paper. This paper begins by studying two common techniques of class schedule through SMS, which are addressed on SMS via cellular modem and SMS via gateway. It will describe the system architecture of these techniques include how they were implemented, it’s strengths and weaknesses in main aspects such as network interoperability and messaging cost. From these two techniques, the studies will come out with an appropriate technique solution for the class schedule via SMS for the student convenience, which considered the cost-effective and practical factors. Finally, the paper reports on the finding of a new prototype of SMS class schedule technique that will benefit students and lectures in terms of fast delivery of class schedule, reliable and effective cost communication for concise information.